Shutter of the Artesanian Well Gushing Abandons in Monzoungoudo, Benin - HOUNTONDJI, Babilas; CODO, François de Paule; AINA, Martin Pépin (GeoScience Engineering, 2021)
The artesian well of Monzoungoudo has been abandoned since 2005. The non-mastery of artesianism springing up at this water point constitutes a waste of the resource and has caused environmental damage. It is a question of an uncontrolled flow of the artesian well induced by the depressurization of the aquifer, resulting in a potential loss of capacity of neighbouring wells and continuous flow of the well at the mouth of its casing. In contact of the recovered water with the surrounding soil, it may generate local flooding, gullying, soil subsidence, the formation of sinkholes and cause damage to the infrastructures located nearby. In addition, the water from the artesian aquifer on the surface migrates to the Monzoun River, while transporting suspended particles or contaminants encountered on its path. The receiving environment of this water could then be affected by an input of turbid water or various contaminants. All these reasons justify the validity of this study, which proposes to address the technique of plugging the abandoned artesian wells of Monzoungoudo in order to stop or control the gushing water. Keywords: Abandons; Artesian well; Captive aquifer; Gushing; Monzoungoudo; Shutter.